AI-Driven DRC Routing Convergence in IC Design : A Paradigm Shift in Semiconductor Development - Srivatsan Nurani Subramanyam (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the transformative impact of Artificial Intelligence (AI) on Integrated Circuit (IC) design, particularly in Design Rule Checking (DRC) and routing convergence. As semiconductor technology advances to smaller nodes, traditional design methodologies struggle with increasing complexity, time-to-market pressures, and stringent manufacturing constraints. Integrating AI-driven approaches offers promising solutions, dramatically reducing design cycles, improving yield, and enabling continued scaling. The article discusses the challenges of modern IC design, the critical role of DRC, and the AI revolution in routing optimization. It examines the benefits of AI-driven DRC routing convergence, including reduced time-to-market, improved design quality, cost reduction, enhanced scalability, and adaptability to new processes. Finally, it addresses current challenges and future research directions in this rapidly evolving field.